y=ln (x-1)^3/(2x+3) y'=3(1/x-1)-(2/2x+3) y'=(3/x+1)-(2/2x+3) answer Is this right? its a problem on a take home test and im just wondering if i got it right. If its not can you point out where.thx
Follow Math Help Forum on Facebook and Google+
Originally Posted by calculusphobe y=ln (x-1)^3/(2x+3) y'=3(1/x-1)-(2/2x+3) y'=(3/x+1)-(2/2x+3) answer Is this right? its a problem on a take home test and im just wondering if i got it right. If its not can you point out where.thx You can check it here: Wolfram|Alpha
View Tag Cloud